Altchek's diagnosis and management of ovarian disorders - Deligdisch, Liane; Kase, Nathan G., 1930-; Cohen, Carmel J. (Cambridge medicine (Series), 2013)
Disorders of the ovary can lead to a wide range of endocrinologic and malignant conditions, many of which are linked with fertility. This comprehensive, yet succinct book presents a multidisciplinary approach to address the major issues in diagnosing and managing ovarian disorders. Beginning with the complex functioning of the normal ovary, the editors address many of the major issues in women's health. New chapters on ovarian cysts, menopause, the aging ovary, early detection and risk assessment of ovarian cancer, screening, stage I ovarian cancer and many other topics have been added to this third edition. Assisted reproductive techniques, diagnostic imaging modalities, minimally invasive surgery, and chemotherapy have advanced dramatically and the chapters have been updated accordingly. This well-documented volume has been fully updated with contemporary references and chapters written by current leaders in their field. A must-read for gynecologists, oncologists, obstetricians, pathologists and researchers in human reproductive sciences.